Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1177/0363546514565097
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Diabetes Mellitus on Clinical and Structural Outcomes After Arthroscopic Rotator Cuff Repair

Abstract: Pain, range of motion, and function all significantly improved after arthroscopic rotator cuff repair using the suture-bridge technique, regardless of the presence of diabetes. However, sustained hyperglycemia increased the possibility of anatomic failure at the repaired cuff. In diabetic patients, an effective glycemic control was associated with better rate of healing after rotator cuff repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(128 citation statements)
references
References 31 publications
(49 reference statements)
3
122
2
1
Order By: Relevance
“…Diabetic patients with tendinopathy were found to have a longer duration of chronic hyperglycemia than those without tendinopathy1. After surgical repair in the rotator cuff, diabetic patients with poorer glycemic control were found to have a higher retear rate24. These findings suggest that long-sustained high concentration of blood glucose is associated with diabetic tendinopathy.…”
Section: Discussionmentioning
confidence: 95%
“…Diabetic patients with tendinopathy were found to have a longer duration of chronic hyperglycemia than those without tendinopathy1. After surgical repair in the rotator cuff, diabetic patients with poorer glycemic control were found to have a higher retear rate24. These findings suggest that long-sustained high concentration of blood glucose is associated with diabetic tendinopathy.…”
Section: Discussionmentioning
confidence: 95%
“…performed a comparative cohort study and demonstrated that patients with diabetes had an significantly increased retear rate (35.9%) following arthroscopic rotator cuff repair surgery as compared to controls (14.4%) as evaluated on MRI (P < .001). 39 These authors also found that effective glycemic control was associated with improved healing rates after rotator cuff repair, with 43.2% in an uncontrolled diabetic patient population (>7.0% hemoglobin A1c) as compared to 25.9% in patients with adequate glycemic control developing re-tears of the repaired tendon.…”
Section: Diabetes Mellitusmentioning
confidence: 91%
“…This is particularly important given that T2DM increases the risk of tendon tear or rupture up to fivefold, relative to non‐diabetics . In terms of healing outcomes in specific tendons, the most abundant clinical data exists in the RC, with clear evidence of diminished healing and increased risk of repair failure (greater than twofold) . There is also some evidence that limitations in healing are particularly pronounced during the early phases of healing.…”
Section: Diabetic Tendon Healingmentioning
confidence: 99%